How much does the public know about the ECB's monetary policy? Evidence from a survey of Dutch households - Carin van der Cruijsen; David-Jan Jansen; Jakob de Haan (European Central Bank (ECB), 2010)
Does the general public know what central banks do? Is this kind of knowledge relevant? Using a survey of Dutch households, we investigate these questions for the case of the European Central Bank (ECB). Our findings suggest that knowledge on the ECB's objectives is far from perfect. Both a weak desire to be informed and unawareness of insufficient knowledge are barriers for improving the public's understanding of monetary policy. However, our results also show that more intensive use of information improves understanding, suggesting that the media channel may play an important and constructive role in building knowledge. Finally, we find that knowledge on monetary policy objectives contributes to an individual's ability to form realistic inflation expectations.
Keywords: D12; D84; E52; E58; 330; ECB; financial literacy; inflation expectations; knowledge; monetary policy; transparency; Geldpolitik; Öffentliche Meinung; Politische Kommunikation; Inflationserwartung; Privater Haushalt; Niederlande